Integrated Study of Transcriptome-wide m6A Methylome Reveals Novel Insights Into the Character and Function of m6A Methylation During Yak Adipocyte Differentiation - Zhang, Yongfeng; Liang, Chunnian; Wu, Xiaoyun; Pei, Jie; Guo, Xian; Chu, Min; Ding, Xuezhi; Bao, Pengjia; Kalwar, Qudratullah; Yan, Ping (Frontiers in Cell and Developmental Biology, 2021)
Yak (Bos grunniens) is considered an iconic symbol of Tibet and high altitude, but they suffer from malnutrition during the cold season that challenges the metabolism of energy. Adipocytes perform a crucial role in maintaining the energy balance and adipocyte differentiation is a complex process involving multiple changes in the expression of genes. N6-methyladenosine (m6A) plays a dynamic role in post-transcription gene expression regulation as the most widespread mRNA modification of the higher eukaryotes. However, currently there is no research existing on the m6A transcriptome-wide map of bovine animals and their potential biological functions in adipocyte differentiation. Therefore, we performed methylated RNA immunoprecipitation sequence (MeRIP-seq) and RNA sequence (RNA-seq) to determine the distinctions in m6A methylation and gene expression during yak adipocyte differentiation. In yak adipocyte and preadipocyte the content of m6A and m6A associated enzymes was substantially different. In the two groups, a total of 14,710 m6A peaks and 13,388 m6A peaks were identified. For the most part, m6A peaks were enriched in stop codons, 3’-untranslated regions and coding regions with consensus motifs of GGACU. The functional enrichment exploration displayed that differentially methylated genes participated in some of the pathways associated with adipogenic metabolism, and several candidate genes (KLF9, FOXO1, ZNF395 and UHRF1) were involved in these pathways. In addition to that there was a positive association between m6A abundance and levels of gene expression, which displayed that m6A may play a vital role in modulating gene expression during yak adipocyte differentiation. Further, in the adipocyte group several methylation gene protein expression levels were significantly higher than in preadipocytes. In short, it could be concluded that the current study provides a comprehensive explanation of the m6A features in the yak transcriptome, offering in-depth insights into m6A topology and associated molecular mechanisms underlying bovine adipocyte differentiation which might be helpful for further understanding its mechanisms.